2003
DOI: 10.1086/376728
|View full text |Cite
|
Sign up to set email alerts
|

A Multiwavelength Study of the High‐Field Magnetic White Dwarf EUVE J0317−85.5 (=RE J0317−853)

Abstract: We present optical and ultraviolet photometry and spectroscopy and optical circular spectropolarimetry of the ultramassive, rapidly rotating, high-field magnetic white dwarf EUVE J0317À85.5. From the combined data sets, we establish an ephemeris for the photometric, spectroscopic, and polarimetric variations with a spin period of 725.7277 s, the fastest yet measured for an isolated white dwarf. We build a series of far-ultraviolet (FUV) and optical flux spectra as well as optical polarization spectra that desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…the highest known temperature of all MWDs with a field strength above 20 MG (Kawka et al 2007;Külebi et al 2009). Barstow et al (1995) performed high-speed photometry demonstrating that the optical brightness of RE J 0317-853 varies almost sinusoidally with a period of 725.4 ± 0.9 s and an amplitude of more than 0. m 1; these results were confirmed by Vennes et al (2003), who inferred a period of 725.727 ± 0.001 s from the variation in the circular polarisation. The only reasonable explanation of these results is rotation, implying that RE J 0317-853 rotates more rapidly than any other known white dwarf that is not a member of a close binary.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…the highest known temperature of all MWDs with a field strength above 20 MG (Kawka et al 2007;Külebi et al 2009). Barstow et al (1995) performed high-speed photometry demonstrating that the optical brightness of RE J 0317-853 varies almost sinusoidally with a period of 725.4 ± 0.9 s and an amplitude of more than 0. m 1; these results were confirmed by Vennes et al (2003), who inferred a period of 725.727 ± 0.001 s from the variation in the circular polarisation. The only reasonable explanation of these results is rotation, implying that RE J 0317-853 rotates more rapidly than any other known white dwarf that is not a member of a close binary.…”
Section: Introductionsupporting
confidence: 58%
“…For RE J 0317-853, it was similarly proposed to explain both the high angular momentum and high mass of this star (Ferrario et al 1997). Vennes et al (2003) also suggested that the scenario could produce a strong and non-dipolar magnetic field. They argued qualitatively that the high angular momentum is a result of the total orbital momentum of a coalescing binary and that the strong nondipolar magnetic field can be generated by dynamo processes due to the differential rotation caused in turn by the merging.…”
Section: Binary Origin Of Re J 0317-853mentioning
confidence: 94%
See 1 more Smart Citation
“…- (1 Barstow et al 1995;(9) Ferrario et al 1997;(10) Vennes et al 2003;(11) Bergeron et al 1992; (12) Vennes 1999; (13) Vennes et al 1999;(14) Vennes et al 1996. vMa 2, which was extracted from the Spitzer archive (program 33; PI: G. G. Fazio). These targets are relatively old, with total ages between 1 and 7 Gyr, and are listed in Table 3 for completeness, although their IRAC fluxes are previously published in Paper I with the exception of vMa 2.…”
Section: Older Targetsmentioning
confidence: 99%
“…It has been suggested that magnetic flux densities up to 10 5 T (1 gigagauss) exist on the surface of white dwarf and cataclysmic variable stars [5][6][7] . This inference is based on a complex process that involves a combination of modelling the pattern of flux around the surface and up through the atmosphere of the star, and a search for transitions that are stationary with magnetic field [2][3][4] .…”
mentioning
confidence: 99%